2023
DOI: 10.7759/cureus.37536
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Endometriosis Awareness in Turkey

Abstract: Introduction: Endometriosis is a chronic painful disease that affects the daily quality of life of individuals. Estimated rates show one in 10 women has endometriosis, although the actual prevalence is unknown. In this study, the impact of endometriosis prevalence and symptoms on women's lives in Turkey was questioned through a web-based questionnaire.Methods: We utilized a version of the World Endometriosis Research Foundation (WERF) EndoCost tool, which was sent to applicants via social media. Data from wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…assessed the prevalence of endometriosis and found that one out of every six women had endometriosis‐related symptoms. Moreover, the prevalence of endometriosis increases by up to 30% in cases with infertility and 45% in cases with chronic pelvic pain 4 …”
Section: Introductionmentioning
confidence: 99%
“…assessed the prevalence of endometriosis and found that one out of every six women had endometriosis‐related symptoms. Moreover, the prevalence of endometriosis increases by up to 30% in cases with infertility and 45% in cases with chronic pelvic pain 4 …”
Section: Introductionmentioning
confidence: 99%